Timing and position of Late Wisconsinan ice-margins on the upper slope seaward of Laurentian Channel - Piper, David; Macdonald, Adam (Géographie physique et Quaternaire, 2001)
AbstractAt the last glacial maximum, the major ice outlet through Laurentian Channel terminated on the upper continental slope. A 10 km square area of the upper slope has been investigated in detail, using airgun and boomer seismic reflection profiles and piston cores. Sediment failure during the 1929 Grand Banks earthquake resulted in exposure at the seabed of Last Glacial Maximum sediments that are normally buried beneath tens of metres of younger strata. Ice-margin acoustic and lithofacies are interpreted using criteria developed on the continental shelf and chronology is provided by AMS radiocarbon dates on in situ mollusc shells. Seismic data show a morainal ridge at 500 mbsl (mbsl = metres below (present) sea level) corresponding to the Last Glacial Maximum ice grounding line. A change in thermal regime of the ice or a subglacial meltwater outburst, at 16.5 ± 0.15 ka (radiocarbon years, -0.4 ka marine reservoir correction applied), resulted in release of sediment-laden meltwater that eroded gullies on the continental slope. This erosion surface is immediately overlain by a prominent stony diamict that extends to about 700 mbsl and may represent till deposition from a glacial surge. The ice margin then retreated upslope by 16.3 ka, probably to the prominent moraine at 380 mbsl at the lip of the Laurentian Channel. Evidence from mud turbidites on Laurentian Fan suggests that this ice marginal position may have persisted until about 14.2 ka. Ice then retreated rapidly northwards up Laurentian Channel, synchronous with Heinrich Event 1 at about 14 ka. Younger proglacial sediment on the upper continental slope slumped at about 12 ka, probably as a result of loading by a late-ice advance across St. Pierre Bank.